The effect of zakat programs on the social impact of microfinance institutions in Bangladesh - Uddin, Md Nazim; Hamdan, Hamdino; Che Embi, Nor Azizan; Kassim, Salina; Md Saad, Norma (Lembaga Zakat Negeri Kedah, 2020)
The purpose of this paper to measure the effectiveness of the central for zakat management (CZM) efforts in utilising zakat funds for promoting microfinance among poor rural people in Bangladesh.Thisstudyassessesthe effectivenessofzakatonaspectssuch asincome, household expense and fixed asset accumulation of the poor client based on the before and after approach groups comprising to impoverished individuals and families are given equity capital and are encouraged to set on small businesses according to their liking and ensure sustainable development goals (SDGs). The group are supervised for a period in 2010 to 2018, ensure all individualswithin the group can continue with their activities and ultimately, free themselves from the shackles of poverty and graduate into a sustainable livelihood and social impact. Results indicate a significant nominal and real increase in average monthly income, an increase in fixed assets and an increase in monthly average household expenditure before and after receiving zakat money. The findings from this paper shed light on the effectiveness of the zakat-based approach in alleviating poverty and ensuring sustainable economic empowerment of the poor rural people. This research is significant as it could be useful in future discussions on the potential ways to improve zakat-based MFIs and SDGs in Bangladesh. The outcomes from the discussions w